2019
DOI: 10.1590/1413-812320182412.08382018
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against influenza among pregnant women in southern Brazil and associated factors

Abstract: This article aims to identify the prevalence and factors associated with influenza vaccination in pregnant women. This is a cross-sectional study conducted in a municipality in the southernmost region of Brazil, which included all women giving birth in 2016. The outcome was having received the vaccine against influenza during pregnancy. Sociodemographic, behavioral and prenatal care characteristics and morbidities were analyzed. The analysis included sample description, the prevalence of vaccination for each i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
(36 reference statements)
0
9
0
3
Order By: Relevance
“…(24,25) Among pregnant women in the city of Rio Grande, the non-vaccination rate in those who did not undergo prenatal care was up to 20 times higher. (27) This reinforces the importance of guidance as to primary prevention, as is highlighted in a systematic review; the probability of non-vaccination is higher in those who interact less with the health system, have fewer medical appointments, and do not have a source of regular care. (12) Those who knew that their household was registered in the Primary Healthcare Unit were less likely to not to be vaccinated, showing a borderline association after adjustments.…”
Section: ❚ Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…(24,25) Among pregnant women in the city of Rio Grande, the non-vaccination rate in those who did not undergo prenatal care was up to 20 times higher. (27) This reinforces the importance of guidance as to primary prevention, as is highlighted in a systematic review; the probability of non-vaccination is higher in those who interact less with the health system, have fewer medical appointments, and do not have a source of regular care. (12) Those who knew that their household was registered in the Primary Healthcare Unit were less likely to not to be vaccinated, showing a borderline association after adjustments.…”
Section: ❚ Resultsmentioning
confidence: 55%
“…There was no relation between non-vaccination and schooling in this sample, unlike what was found in studies, both in Campinas (SP) including the elderly, (22) and in Rio Grande with pregnant women. (27) Therefore, schooling is not necessarily linked to the population's knowledge, based on the benefits of vaccination, considering the educational nature aimed by the campaign of the Ministry of Health. (3,4,28) Even though the harm of smoking is well known, in this sample, 17.5% were smokers.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…Appropriate adjusted estimates were pooled using the inverse variance, random-effects model implemented in STATA version 13 (StataCorp LP) and the pooled adjusted odds ratios (OR) and their 95% confidence intervals (95% CI) are reported both overall and by country. A few studies reported adjusted rate ratios, 30 adjusted prevalence ratios [31][32][33][34][35] and adjusted hazard ratios. 36 It was not possible to convert these statistics to ORs because we did not know the baseline SIV uptake rates between the compared groups.…”
Section: Discussionmentioning
confidence: 99%
“…From a total of 1663 retrieved citations after de-duplication, 34 articles (representing 36 studies) met our eligibility criteria (Figure 1). [30][31][32][33][34][35][36] The articles were published from 2010 to 2020. Eleven articles were from the USA, 30,32,35,41,45,46,48,59,60,65,66 six from Australia, [49][50][51]53,61,63 four from France, 31,43,47,57 two from Canada, 56,62 two from the UK 40,55 and one each from Belgium, 54 Brazil, 33 Greece, 44 Hong Kong, 64 Ireland, 52 Japan, 42 Nicaragua, 58 Singapore 34 and Spain.…”
Section: Re Sultsmentioning
confidence: 99%
“…Benzer biçimde İtalya' da yapılan bir çalışmada orta düzeyde eğitimli gebelerin lisans mezunu gebelere kıyasla influenza aşısı hakkında daha az bilgili olduğu saptanmıştır (18). Gebelerin influenza aşısına yaklaşımına dair bir başka çalışmada ise eğitim süresi ≥12 yıl olanlarda aşılanma oranları diğer gruplara kıyasla daha yüksek bulunmuştur (19) (22). Ölenler arasında, 32'si antepartum 4'ü postpartum dönemde olmak üzere, 36 gebe/lohusa da bulunmaktadır (23).…”
Section: Tartişma Ve Sonuçunclassified